ВЛИЯНИЕ СКОТОВОДЧЕСКОГО ХОЗЯЙСТВА НА ЗООЛАТРИЧЕСКИЕ ВЕРОВАНИЯ В АЗЕРБАЙДЖАНЕ В VI-III ТЫСЯЧЕЛЕТИИ ДО Н.Э. - Гулузаде, Н. В. (Journal of Oriental Studies, 2016)
In the given article questions on changes in zoolatry ideas and cults of ancient times in connection with development of cattle-breeding in Azerbaijan in the period of eneolit and early bronze are considered. Author mainly gives consideration to the period of development of production economies in Azerbaijan, when totemist cults gradually lose their positions in ideological Вест ник КазНУ. Серия востоковедения. №2(55). 2011 13 ideas of that time and their place in the cults and ceremonies which positively influence the development of cattle-breeding. In the article development of zoolatry cults is described using archeological and ethnographic materials.